THE EFFECT OF TEACHER ORAL CORRECTIVE FEEDBACK ON STUDENTS’ PRONUNCIATION - Azzahra Meyditha Salsabila; Haryanto; Geminastiti Sakkir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This study aims to find out whether there is a significant effect of teacher oral corrective feedback on students' pronunciation. The researcher applied pre-experimental method also to achieve the research objectives, data collection was conducted through pre-test and post-test that designed to evaluate four main aspects of pronunciation, namely accuracy, clarity, intonation and word stress. Pronunciation scores are assessed using a 1-5 scale on each aspect. The population of this study was all ninth grade students of SMPN 27 Makassar that consisted of 11 classes with a total of 341 students and the sample of this study consisted of 30 students of class IX.2 at SMPN 27 Makassar that selected by purposive sampling technique. The results of the pre-test and post-test of students' English pronunciation through the provision of oral corrective feedback treatment after being analyzed by T-Test showed a probability value of 0.000 which was significantly lower than the level of significance (0.05), so the alternative hypothesis (Ha) was accepted, and after being analyzed by N-Gain value, the results showed a result of 0.24 which was lower or <0.30 therefore, the improvement that occurred in the pronunciation of the students in the sample group was at a low level.